2019
DOI: 10.1002/jrsm.1354
|View full text |Cite
|
Sign up to set email alerts
|

Best practice guidelines for abstract screening large‐evidence systematic reviews and meta‐analyses

Abstract: screening is one important aspect of conducting a high‐quality and comprehensive systematic review and meta‐analysis. Abstract screening allows the review team to conduct the tedious but vital first step to synthesize the extant literature: winnowing down the overwhelming amalgamation of citations discovered through research databases to the citations that should be “full‐text” screened and eventually included in the review. Although it is a critical process, few guidelines have been put forth since the public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
126
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 23 publications
0
126
0
2
Order By: Relevance
“…Without having a correlation one cannot compute a standardized mean difference between pre-post scores and consequently, a study without this information cannot be meta-analyzed (Borenstein et al, 2009). This is not an uncommon predicament for a synthesist to find oneself in (Polanin, 2012). In order to include these studies in the current meta-analysis a pre-post correlation needed to be imputed (Polanin, 2012).…”
Section: Mhcsmentioning
confidence: 99%
See 4 more Smart Citations
“…Without having a correlation one cannot compute a standardized mean difference between pre-post scores and consequently, a study without this information cannot be meta-analyzed (Borenstein et al, 2009). This is not an uncommon predicament for a synthesist to find oneself in (Polanin, 2012). In order to include these studies in the current meta-analysis a pre-post correlation needed to be imputed (Polanin, 2012).…”
Section: Mhcsmentioning
confidence: 99%
“…This is not an uncommon predicament for a synthesist to find oneself in (Polanin, 2012). In order to include these studies in the current meta-analysis a pre-post correlation needed to be imputed (Polanin, 2012). The average correlation between pre-post scores was calculated from the studies that reported pre-post correlations and this average (.295) was used as the correlation for the other studies (Polanin, 2012).…”
Section: Mhcsmentioning
confidence: 99%
See 3 more Smart Citations